Analysis of modern strategies for using artificial intelligence technologies in the creation of fantasy content. - Sultan, Yertay; Dautova, Gulnaz; Alkebayeva, Dina; Akzhigitova, Akkibat; Aden, Zhansaya (Digital Scholarship in the Humanities, 2025)
This study explores the integration of artificial intelligence (AI) in the creation of fantasy narratives, examining the new possibilities AI offers for authors and readers and its impact on the genre's evolution. The study used literature review, textual analysis, comparative analysis, data analysis, experimental methods, ethical and legal examination, and data processing methods using Natural Language Processing software. Through analysis of films, video games, and qualitative text review, the research found that modern technologies—particularly AI and computer graphics—have greatly enhanced the visualization of fantasy worlds, contributing to the genre's growing popularity. Interactive AI-driven platforms enable customized experiences, increasing engagement and satisfaction among audiences. A significant finding is that contemporary fantasy works, while retaining traditional elements like the struggle between good and evil, magic, and adventure, are now incorporating modern socio-cultural and political themes. This blend preserves the genre's appeal to diverse audiences while keeping it relevant in today's context. Additionally, AI opens new avenues for authors by aiding in overcoming creative blocks, generating fresh ideas, and constructing interactive worlds where readers can shape the plot or create their own characters. This not only accelerates the creative process but also enriches storytelling with more varied narratives. The study concludes that fantasy remains a powerful tool for cultural and social expression and that AI holds great potential for the genre's future growth, promising more innovative and inclusive experiences for audiences.